Right to Die - Singh Thakur, Shobha (International Journal of Psychosocial Rehabilitation, 2021)
Right to life may be a basic natural right of the citizenry. it’s a basic right warranted underneath Part-III (Article 21) of the Indian Constitution. Article 21 of the Indian Constitution states that “no person shall be bereft of his life or personal liberty except in step with procedure established by law”. The phrasing is also negative, however it’s presented an obligation on the state to make sure sensible quality of life and a dignified life to the individuals, that is that the positive side of the article. The foreigners are the maximum amount entitled to the proper because the voters. Now this right to life has been taken by the Indian judiciary in numerous ways that thus on embody inside its scope many new rights comparable to the proper to measure with human dignity, right to resource, right to shelter, right to privacy, right to food, right to education, right to induce pollution free air and water and a few alternative rights that are quite essential to boost the condition of the lifetime of the individuals, i.e. - for actuality enjoyment of the proper to life. But will this right to life be taken to such an extent that ends up in its self destruction or self opposition? that’s, will it embody inside its range the proper to not live or the right to die? this is often the crucial purpose wherever the controversy arises involving ethical, legal, medical and even political problems.